INVENTORY AND IDENTIFICATION OF NTFPS IN THE RED RIVER PROTECTED FOREST AS THE BASIS FOR DEVELOPING COMMUNITY EMPOWERMENT PROGRAMS - Heripan, Heripan; Yuningsih, Lulu; Al Pasha, Ikbal (Sylva Jurnal Ilmu-ilmu Kehutanan, 2022)
The Sungai Merah Protection Forest is close to community settlements. As the population increases, the need for arable land will also increase, so that many people cultivate protected forests into arable land in the form of plantations. On this basis, through the NTFP development program with a community empowerment pattern, it is hoped that protected forests can provide social and economic functions for the community while still paying attention to their ecological functions. In preparing the NTFP development program it is not yet known and there is no data on potential NTFPs that can be developed. This study aims to inventory and identify the types of each non-timber forest product species recorded (classification and nomenclature, morphological characteristics and the beneficial value of the species) of non-timber forest products (HHBK) in the Sungai Merah Protection Forest. The sampling method was carried out by purposive sampling. The selection of samples is based on classification or cluster based on the classification of land cover types resulting from the interpretation of images using GIS software. The sampling intensity to be used is 0.1%. The plot size to be used refers to the guidelines for surveying natural forests and community cultivated plants, namely a plot area of 0.1 ha with a rectangular plot shape (20x50) meters. Rectangular plot shape 20 x 50 m (0.1 ha). the results of data analysis on NTFP secondary forest were dominated by shuji plants, the highest Relative Density (KR), Relative Frequency (FR) and Importance Value Index (INP), namely 28.72%, 20.14% and 48.86 respectively %., while the plantation area was dominated by rubber plants with density, frequency, and dominance of 80.00, 0.25, and 18003.10. This shows the important role of these plants in the protected forest area of the Red River.